Social Cultural Interaction in Harmony Between Religious People in Central Sulawesi - Sidik Sidik (IBDA` : Jurnal Kajian Islam dan Budaya, 2021)
Social and cultural interactions in social activities, cooperation, consensus decision-making, caring for others, and the environment can maintain religious harmony in the people of South Lore and West Lore Districts, Poso Regency. The social and cultural interactions can form a collective consciousness of the community to understand, respect, and appreciate religious diversity. Not surprisingly, if the social and cultural interactions are firmly in three activities in the community: traditional activities where social interaction occurs because the community respects local customs; humanity where through respect for humanity between communities, this social and cultural interaction occurs; and religion that regulates religious relations between communities that respect each other and respect the activities that the community carries out. From these three activities, the social and cultural interaction between community members in South Lore and West Lore Districts, Poso Regency can eliminate the potential for religious conflict and maintain harmony and harmony among various religious believers ot adherents.